การพัฒนาอัตลักษณ์นิสิตนักศึกษาในสถาบันอุดมศึกษา - สุภัชฌาน์ ศรีเอี่ยม (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The current study is conducted as the descriptive research with quasi-experimental design. The objectives of the study are 1) to explore identities of students in higher education institutes, 2) to develop those identities, and 3) to compare the results gained from the experimental group and control group for the identity development in students. The total population of the research is 49,431 students studying at first year level in higher education institutes from both private and public sections. The sampling method employed is simple random method and the size of the sample is calculated through Yamane Table where the reliability level is at 95% and error is at ±4%. Consequently, the size of the sample obtained is 621 students. The sample group is 60 students studying at first year level in Eastern Asia University. The instrument employed is the newly developed assessment called as "Higher Education Students’ Identity Self-Assessment and Development" of which the content’s reliability is analyzed through content analysis. The descriptive statistics used are percentage, mean, standard deviation, and t-test. The results obtained can be concluded as follows. Regarding to the studying of the current identities of the students in higher education institutes, it is found that the overall positive identities are reported at "very true" level while the negative identities are reported at "fairly true" level. As for the identities needed for the development, they are; namely, life target (the drive for development of students’ identifies in each angle; namely, individualism, socialism, living, and academy), problem evaluation (the problem should be evaluated by the organization, stake holders in the university and faculty), need analysis for training (the creation of training program, activity design, administration, and evaluation concerning the development of students’ identity), evaluation of the activities for each part of students’ identity, and the comparison of the results gained from the development of students’ identity in higher education institute. The experimental group joining the program for identity development of this research possesses the average score with statistical difference from the control group at 0.05, and the experimental group performs the score differently between before and after joining the program with the statistical difference at 0.05.